Understanding Aspheric Lenses: Key specifications and their impact on performance. Issue 4 (24th October 2018) - Adams, Daniel; Ament, Shelby
Abstract: Aspheric lenses are an extremely powerful tool for improving the performance of optical systems whilst also reducing the number of elements and consequently size and weight. From medical equipment and microscopes to smart phones and autonomous vehicles, they are increasingly important across all optics‐enabled industries. An aspheric surface cannot be made in the same way as a spherical one, a range of sub‐aperture grinding and polishing techniques must be used to create a variable curvature. These methods create additional issues that need to be monitored and controlled to maximize the performance of an aspheric lens.